A dynamic model of Nordic diagonal stride skiing, with a literature review of cross country skiing - Hausken, K. (Computer Methods in Biomechanics and Biomedical Engineering, 2009)
The forces during the kicking phase in Nordic diagonal stride skiing are described by differential equations and the results are compared with experiments. The difference between static and dynamic friction, interacting with characteristics of the skier such as weight, velocity and the kicking force's angle with the terrain, are essential for high-velocity diagonal striding. Analytical results for relationships between glide length, friction and kicking force are shown. Aerodynamic drag and gravity are accounted for. A propulsion force based on the Hill (1970) equation for muscle contraction velocity and activation is constructed. The model shows a feasible tool for studying the effects of ski stiffness, the kicking force and the amount of waxing during diagonal stride skiing.